Imported infectious diseases : the impact in developed countries - Cobo Martínez, Fernando (Woodhead Publishing, an imprint of Elsevier, 2014)
The increase of immigrant population in developed countries (mainly in Europe and North America) together with an important increase of international travel worldwide are the two most important causes that have contributed to the introduction and diagnosis of imported/tropical infectious diseases in these countries. These factors have had an important impact in developed countries in both social and economic aspects. Imported Infectious Diseases focuses not only on describing the infections, but also in evaluating the current epidemiology, the economic and social impact and the possibility to apply immunization measures and vaccines. The main purpose of this book is to give an overview of the current most important and frequent imported infectious diseases in developed countries. The first chapter informs about the medical services that are being offered to the immigrants in the main developed countries depending on the legal situation. Following chapters describe the main surveillance systems for these kinds of diseases, mainly in Europe and North America. Finally, remaining chapters contain sections on epidemiology, pathogenesis, clinical features, diagnosis, treatment and prevention.
Woodhead publishing series in biomedicine ; number 66
Keywords: infekční nemoci; rozvojové země; Population Surveillance; Emigrants and Immigrants; Endemic Diseases; socioekonomické faktory; surveillance populace; Disease Transmission, Infectious; tropické lékařství; infekční lékařství; Developing Countries; Socioeconomic Factors; endemické nemoci; Tropical Medicine; Communicable Diseases; přenos infekční nemoci; emigranti a imigranti